In praise of a historical storytelling approach in science education - Gamito-Marques, Daniel (2021)
In the 1970s and 1980s, the use of history of science in science education was controversial. In the three last decades attitudes have changed, but the question of best practice has not been definitively answered: What type of historical knowledge should be incorporated in pedagogical contexts, and how? This essay discusses features of historically informed narratives that are suitable for teaching science from upper secondary education on, looking in particular at cases in the history of biology. The essay argues that such narratives should focus on the evolution of fundamental concepts and theories in a given scientific discipline, not on the life and work of one or a few scientists; that a story’s historical content must be carefully selected and heavily contextualized in order to serve pedagogical needs; and that storytelling techniques should be actively used to engage students.